MULTI MEDIA AKSES (MMA) - Agoes, Suhartati; Ningsih, Yuli Kurnia (Jurnal Teknik Elektro, 2001)
The very high necessity of information force the development of information technologyespecially internet. Nevertheless, POTS still cannot satisfy their customers. The main factorwhich cause this problem is the internet access speed limitedness. Besides the telephone calland internet access must be used by turns. MMA offers high speed internet access by usingADSL lite technology and ATM to support various of multimedia applications. MMA alsoenable to use internet access and telephone simultaneously without need new customersâline.As a service which offers high speed internet access, so in this paper some experimentsof MMA access speed have been done. The conclusion of the experiment are internet accessspeed is not influences neither by the file size nor by using internet access and telephone callsimultaneously.Keywords: Data off loading, Asynchronous Transfer Mode (ATM), Asymmetric DigitalSubscriber Line (ADSL)